A group strategy‐proof incentive approach for eliminating selfish behaviors in peer‐to‐peer file allocation. (3rd May 2013) - Zuo, Fang; Zhang, Wei
SUMMARY In this paper, we formulate and solve the selfish allocation problem by using game theory, which is different from the previously studied researches in three ways that make it more accurately reflective of real world peer‐to‐peer (P2P) allocation: (i) we treat the nodes as strategic agents and treat the replica allocation as a deliberate auction where node is incentivized to give his true quality of service for obtaining the replica; (ii) our mechanism computes node utility for all possible replica destination and payments for those destination nodes, and the best appropriate node can be selected as the final placement destination; and (iii) we show how to carry out our scheme with a distributed algorithm that is a straightforward extension to P2P allocation method and causes an overhead in convergence time. Our design and analysis of a strategy proof, feasible, Vickrey–Clarke–Groves‐based auction scheme provides a new, promising direction in distributed algorithmic mechanism design, which has heretofore been focused mainly on P2P application. Copyright © 2013 John Wiley & Sons, Ltd.